The influence of gross profit margin, net profit margin, company size, and sales growth on profit growth (in manufacturing companies registered on bei in 2019-2022) - Gulo, Juwita; Sembiring, Jessi Charina (ProBisnis : Jurnal Manajemen, 2024)
The aim of the research is to analyze the influence of gross profit margin, net profit margin, company size and sales growth on profit growth (in manufacturing companies listed on the IDX in 2019-2022). The research was produced using secondary data and a purposive sampling method, namely the researcher carried out the best assessment to fulfill what had been determined, using a quantitative assessment approach, the total sample was 11 companies. The data was analyzed using multiple linear analysis techniques via the SPSS 23 application. The research results stated that GPM, NPM, company size and sales growth simultaneously and significantly influenced profit growth (in manufacturing companies listed on the BEI in 2019-2022). Gross Profit Margin, Net Profit Margin, Sales Growth have a partial and significant influence on Profit Growth (in manufacturing companies listed on the IDX in 2019-2022). Company size has no influence and is not partially significant on Profit Growth (in manufacturing companies listed on the IDX for the 2019-2022 period).